Strategic Action in the Liberalised German Electricity Market - Wietze Lise; Claudia Kemfert; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2003)
Nowadays, a process can be observed in Germany where electricity producing and trading firms react to the electricity market liberalisation by merging market shares, since the year 2000, which reduces the number of suppliers and influences production and consumer prices. This paper discusses whether the liberalisation process will have positive or negative impacts on the environmental situation and whether this process together with a phase out of nuclear power can guarantee the intended improvement of environmental conditions without governmental regulation in Germany. This is done by modelling different strategic options of energy suppliers and their impacts on the economic and environmental situation in the liberalised German electricity market by a computational game theoretic model. Calculations with this model show that when German firms act strategically (e.g. a change in action of one firm affects the electricity price and, hence, the payoffs of other firms), the environment is better off at the cost of higher electricity prices. This result is robust to perturbations as shows by performing a sensitivity analysis.
Keywords: C7; D2; Q4; R3; 330; Electricity market liberalisation; game theoretic model; environmental effectiveness; Elektrizitätswirtschaft; Deregulierung; Spieltheorie; Umweltbelastung; Deutschland